Localized retroperitoneal Rosai-Dorfman-Destombes disease as a cause of fever of unknown origin in adults. Case report and review of the literature. (August 2022) - Popivanov, Georgi; Baymakova, Magdalena; Bochev, Pavel; Penchev, Dimitar; Konaktchieva, Marina; Mutafchiyski, Ventsislav
Abstract: Introduction: Rosai-Dorfman-Destombes disease (RDD) is a rare "R" group histiocytic disease with a prevalence of 1:200, 000. Herein, we present an extr4mely rare case with localized retroperitoneal RDD manifested as a fever of unknown origin (FUO). This case was managed in an academic setting and illustrates the challenging diagnostics of RDD and FUO. Presentation of case: A 53-years-old female was admitted with complaints of night sweats, fever to 39.5 °C, 10 kg weight loss, fatigue, weakness, abdominal discomfort, and headache. On physical examination, there was no peripheral lymphadenomegaly or liver or spleen enlargement. Blood analysis revealed a hemoglobin 10.8 g/dL, elevated C-reactive protein level of 100.6 mg/L, and fibrinogen 6.57 g/L. Blood, throat, and urine cultures and serology tests were negative. Abdominal ultrasonography, transthoracic echocardiography, radiography, and computed tomography of the abdomen were normal. The PET scan showed a retroperitoneal conglomerate on the left side of the aorta. Subtotal resection of the conglomerate was performed. Microscopic examination revealed dilated sinusoids containing a large number of S100+ and CD68+ histiocytes, with marked emperipolesis. The patient recovered uneventfully. Eight months later, she was afebrile and free of complaints, with a 5 kg weight gain and negative PET/CT findings. Conclusion: Localized abdominal RDD can cause FUO and should be considered in the differential diagnosis of localized retroperitoneal masses. PET/CT is useful for diagnosis, staging, and follow-up. Surgery is indicated for biopsy in cases of diagnostic uncertainty or decompression in symptomatic extranodal forms, but can be a definitive treatment for localized RDD. Highlights: The localized abdominal RDD could be a possible cause of FUO. RDD should be considered in the differential diagnosis of localized retroperitoneal mass and FUO. FDG-PET/CT is a useful diagnostic tool for initial diagnosis, staging, and follow-up. In localized RDD, the surgery can be a definitive treatment.